Educational administration materials in the U.P. College of Education Library an analysis by date, place of publication and content areas - Chanthong, Chintana 1943-
Actual examination of records and materials and gathering of data on all the materials in educational administration through the card catalogue and shelflist resulted in analysis of the materials by format, content area, and place, and year of publication. Ninety percent of the books on educational administration in the College of Education Library were published in the United States. Seventy-one theses and dissertations deal with personnelmanagement and organization and management. Subscriptions to 14 out of 34 periodical titles have been terminated.